Asset Optimization Strategy of the Technical Implementation Unit of The Cultural Park and Museum of the Regional Education and Culture Agency of the West Sulawesi Province - Idris DP, Muhammad; Bombing, Andyka Eka Putra; Nurdin, Wahyu Nurdiansyah; Azmi, Ilima Fitri (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
Asset optimization in asset management seeks to maximize an asset’s physical, legal, and economic potential through proper management, procedures, and utilization. The Technical Implementation Unit of the Cultural Park and Museum of the Regional Education and Culture Agency of West Sulawesi Province has not yet conducted asset valuation or implemented leasing mechanisms, resulting in suboptimal revenue generation. This study examines how asset optimization can be strengthened through improved management, procedural implementation, and utilization forms. Using a qualitative descriptive design, data were collected through interviews, observation, and documentation involving eight informants. Findings indicate that planning, asset utilization, lending, and cooperation-based utilization have been implemented, although not yet supported by valuation and leasing practices. The study recommends conducting asset valuations, formalizing lease implementation, and integrating leasing with lending and cooperation systems to enhance revenue. Proper adoption of these strategies can position the Unit as a more productive cultural service institution.